(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
Modern agriculture is focused on the introduction of energy-saving, rational and environmentally friendly agricultural technologies. Recently, more and more attention has been paid to preserving the fertility of agricultural land. One of the most pressing issues facing agricultural enterprises and farmers is excessive soil compaction. This problem is caused by the increasing weight and size of agricultural machinery, which leads to compaction of not only the arable but also the subsoil layer. The depth of compaction depends on a number of factors, including the weight of tractors, the number of passes of machinery, moisture, soil type and physical condition. In addition, intensive ploughing at a steady depth results in the formation of a so-called ‘plough sole’ with a hardness of more than 3.5 MPa. This condition of the soil prevents capillary moisture from rising from deeper layers, which negatively affects the water supply of crop root systems. One of the most effective ways to combat soil compaction is deep loosening (chiselling), also known as vertical tillage. This technology helps to improve the water and air regime of the soil and, under certain conditions, can serve as an alternative to traditional ploughing. This publication examines the load dynamics on deep-rippers used to break up compacted layers in modern tillage systems. The study was carried out using a measuring and recording complex developed at the university, which provides real-time monitoring of machine load parameters without the need to modify its design. This approach allows us to obtain reliable data for further improvement of agricultural processes.